An outline of technocracy - Parrish, Wayne W. (Farrar & Rinehart, 1933)
This book introduces about the challenge of technocracy, research or propaganda, our energy civilization, the obsolescent man hour, the obsolescent dollar, the profit hurdle, the namesis of debt, the energy yardstick, the north american area, engineers to the front, will technocracy live.